STABILITY INDICATING RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF DOSULEPIN HYDROCHLORIDE AND METHYLCOBALAMIN IN TABLET DOSAGE FORM - Shah, Radhika; Shah, Ragin (International Journal of Applied Pharmaceutics, 2017)
Objective: To develop an accurate, simple, rapid, precise, economic and stability indicating RP-HPLC method for the simultaneous estimation of dosulepin hydrochloride and methylcobalamin in tablet dosage form and validate as per ICH guidelines. Methods: The column used was Kromasil C18 (250 X 4.6 mm, 5 µm), with a mobile phase containing acetonitrile: phosphate buffer pH 3 adjusted with o-phosphoric acid (60:40) with a flow rate of 1 ml/min. The effluents obtained were monitored at 285 nm with photodiode array detector. Dosulepin hydrochloride and methylcobalamin were subjected to stress degradation conditions like hydrolysis (acid and base), oxidation, thermal and photolysis degradation. The samples subjected to stress degradation were analysed by the developed method. Results: The retention time for dosulepin hydrochloride and methylcobalamin was found to be 7.99 min and 1.97 min, respectively. The linearity of developed method was achieved in the range of 165-495 μg/ml for dosulepin hydrochloride and 5-15 μg/ml for methylcobalamin. The detection (LOD) and quantitation (LOQ) limits were found to be 0.75 µg/ml and 2.28 µg/ml for dosulepin hydrochloride and 0.040 µg/ml and 0.121 µg/ml for methylcobalamin respectively. In the stability studies, it was observed that there is no interference of the degradation products with drug samples. Conclusion: An accurate simple, rapid, precise, linear and stability indicating RP-HPLC method was developed for simultaneous quantitative estimation of dosulepin hydrochloride and methylcobalamin both in bulk and pharmaceutical formulation. The method was validated as per ICH guidelines. This method holds good for the routine analysis of dosulepin hydrochloride and methylcobalamin in various pharmaceutical industries as well as in academics.